2021
DOI: 10.1001/jamapsychiatry.2021.2573
|View full text |Cite|
|
Sign up to set email alerts
|

Perturbations in Gut Microbiota Composition in Psychiatric Disorders

Abstract: This systematic review and meta-analysis reviews gut microbiota alterations in general adult psychiatric populations and performs a within- and between-diagnostic comparison.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
257
4
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 421 publications
(316 citation statements)
references
References 92 publications
18
257
4
2
Order By: Relevance
“…In keeping with an interconnected systems based psychiatry paradigm that conceptualizes the individual as a complex composite of interacting systems across all levels of organization, it has been proposed that the microbial ecosystem (microbiome) may serve as an additional transdiagnostic unit of analysis in the RDoC framework (355,356). At the interface between the individual and the environment, the microbiome is intrinsically linked to human health and may play a contributory physiological role in some psychiatric disorders (357)(358)(359).…”
Section: Psilocybiome-an Additional Unit Of Analysis?mentioning
confidence: 99%
“…In keeping with an interconnected systems based psychiatry paradigm that conceptualizes the individual as a complex composite of interacting systems across all levels of organization, it has been proposed that the microbial ecosystem (microbiome) may serve as an additional transdiagnostic unit of analysis in the RDoC framework (355,356). At the interface between the individual and the environment, the microbiome is intrinsically linked to human health and may play a contributory physiological role in some psychiatric disorders (357)(358)(359).…”
Section: Psilocybiome-an Additional Unit Of Analysis?mentioning
confidence: 99%
“…Recent years saw a growing interest in the potential role of the gut microbiota in mental health, notably in schizophrenia. Nikolova et al [ 7 ] suggested a transdiagnostic commonality of microbial disturbances in certain psychiatric disorders including schizophrenia. It would be characterized by a depletion of anti-inflammatory butyrate-producing bacteria and an enrichment of proinflammatory bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, the enterotype B1, and those dominated by Prevotella and Ruminococcus, show a lower incidence in depressed people than in healthy subjects [65]. A very recent meta-analysis has confirmed this perspective [1].…”
Section: Enterotype B2 and Its Possible Correlation With The Anxiety-depressive Syndromementioning
confidence: 96%
“…However, it is undeniable that, despite these differences in methods, some "facts" could still be considered as, if not consolidated, at least as in the process of being consolidated. For example, a recent meta-analysis has confirmed the strong correlation between a certain structure of the colon fecal microbiota and the possible diagnosis of depression [1]. Elements, such as lower biodiversity, lower representation of the phylum Firmicutes, and the lower presence of butyrate-producer taxa, such as Faecalibacterium and Coprococcus, in fact, seem to unite the microbiota of these subjects.…”
Section: Introductionmentioning
confidence: 97%